(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
Scientific approach in archaeological research is crucial in interpreting archaeological data. X-Ray application in characterising particular material assists archaeologists in discovering the raw material, technology applied usage and other parameters. The Earth Material Characterisation Laboratory at the Center of Archaeological Research at USM provides chemical and mineral analysis of archaeological samples qualitatively and quantitatively using Scanning Electron Microscope (SEM), X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD). This article further discusses the types of analysis and applications that can be implemented to archaeological samples from Sungai Batu archaeological site in Kedah. Keywords: x-ray, SEM, XRD, XRF